SOCIO-ECONOMIC FACTOR THAT INFLUENCING FARMING BEHAVIOUR AND FARMER PARTICIPATION LEVEL ON ENVIRONMENTAL MANAGEMENT IN BAUMATA VILLAGE, KUPANG DISTRICT - Hendrik Ernantje; M R Pellokila; L. M Riwu Kaho (Jurnal Ilmu Lingkungan, 2015)
In an attempt to increase agricultural productivity and environtment, it is important to understand farmers’ behaviour and participation in agri-environmental management.   The study was conducted to analyze the influence of sosio-economic factor on farming behaviour and participation in agri-environmental management in Baumata village, Kupang District, Kupang, East Nusa Tenggara Province. The aims of this research were: 1) To find out sosio-economic factors influencing farming behaviour and participation; 2) To find out the relationship between farming behaviors and participation through environmental management. This research was a survey study of descriptive method, with samples were farmers who live and farming in Baumata Village. The respondents were 75 farmers household chosen with a ramdom sampling technique. Data analysis were conducted with Chi Square methods and Spearman Rank Correlation. Results showed that farming behaviours mean score were 17,84 (medium). The socio-economic characteristics influenced farmer’s behaviour in  agricultural activities were: age (χ2= 10,306; df = 2; p = 0,006), farming experience (χ2 = 10,720; df = 2; p = 0,005) and income (χ2 = 10,505; df = 2; p = 0,005);  while the socio-economic characteristics  that did not influence  farmer’s behaviour in agricultural activities were: education  (χ2 = 2,725; df = 4; p = 0,605), family size (χ2= 5,096 ; df = 4; p = 0,278). Participation in environmental management mean score was 17,33 (medium), there was no socio-economic characteristics  that  influence  farmer’s participation, while the socio-economic characteristics  that did not influence farmer’s participation in environmental management were: age (χ2 = 2,995; df = 2; sig = 0,224 ), education (χ2 = 4,504; df = 2; p = 0,105), family size (χ2 = 0,667; df = 2; p = 0,716), farming experience (χ2 = 2,575; df = 2; p = 0,276), and income  (χ2 = 2,150; df = 4; p = 0,341). Spearman Rank Correlation test result showed that there was significant relation between farming behaviours with level of participation in environmental manajement (rs = 0,383; p = 0,001).